Effects of components on and predictive modeling of microemulsion phase behavior in nonionic systems - Prapaporn Boonme, Chalida Boonthongchuay, Thanaporn Amnuaikit and WibulWongpoowarak (Journal of Applied Pharmaceutical Science, 2013)
This study aimed to investigate phase behaviors, to study effects of cosolvent addition on size of microemulsion regions and to propose modified logistic regression which could describe microemulsion regions in nonionic systems. The systems composed of rice bran oil (RBO) or isopropyl palmitate (IPP), various ratios of sorbitan monooleate (SMO) and polyoxyethylene 20 sorbitan monooleate (PSMO) mixtures, water and isopropyl alcohol (IPA) or propylene glycol (PG) were studied for their microemulsion regions obtained on the phase diagrams. Concept of modified logistic regression was used to predict probability of microemulsion formation and size of microemulsion regions in the systems. It was found that both oil and cosolvent types affected on microemulsion formation. A system composed of IPP, 2:1 water:IPA, and 1:1 SMO:PSMO could provide the largest microemulsion region. However, the purposed modified logistic regression could be used consistently for only one system of the total four systems due to the faceted shape of microemulsion-zone.
Keywords: Cosolvent, Microemulsion, Phase behavior, Predictive